Visuomotor Interactions and Perceptual Judgments in Virtual Reality Simulating Different Levels of Gravity - La Scaleia, Barbara; Ceccarelli, Francesca; Lacquaniti, Francesco; Zago, Myrka (Frontiers in Bioengineering and Biotechnology, 2020)
Virtual reality is used to manipulate sensorimotor interactions in a controlled manner. A critical issue is represented by the extent to which virtual scenarios must conform to physical realism to allow physiologically-inspired human-machine interactions. Earth gravity is a constraint of special significance in most sensorimotor contexts. There is ample evidence that the effects of Earth gravity are taken into account in motor tasks. Instead, the evidence that perception of dynamic stimuli is also affected by the assumption of gravity effects is mixed. We asked participants to hit a virtual ball rolling down an incline and falling in air, and to report whether ball motion was perceived as natural or unnatural. Ball motion unrolled under Earth gravity (g), half (g/2) or twice its value (2g). Gravity level was manipulated independently for the motion on the incline and in air, yielding five experimental conditions. In three coherent conditions, gravity was the same during both rolling and falling phases. In two incoherent conditions, rolling was at g, and falling was at g/2 or 2g. The ball was always visible during rolling, but it was visible or occluded during falling before interception. The scene included several cues allowing metric calibration of visual space and motion. We found that the perception rate of natural motion was significantly higher and less variable when ball kinematics was congruent with Earth gravity during both rolling and falling. Moreover, the timing of target interception was accurate only in this condition. Neither naturalness perception nor interception timing depended significantly on whether the target was visible during free-fall; even when occluded, free-fall under natural gravity was correctly extrapolated from the preceding, visible phase of rolling motion. Naturalness perception depended on motor performance, in addition to the gravity condition. In sum, similarly to motor responses, also perceptual responses are guided by internal models of physics allowing the prediction of events unfolding under Earth gravity. To enhance perceptual sensitivity to physical realism, visual backgrounds with rich contextual cues and closed-loop sensorimotor interactions should preferably be used, especially in view of designing physiologically-inspired protocols for basic research and rehabilitation.